1 - New Members of CODESRIA Scientific Committee - Journal System (CODESRIA Bulletin, 2025)
The Scientific Committee (SC) is a charter organ of the Council. It derives its mandate from Article 26 of the charter. It is an advisory committee that counsels the Executive Committee (EC) and Executive Secretariat on scientific matters. It is also responsible for the scientific evaluation of CODESRIA’s programmes and contributes to the development of the Council’s scientific agenda. It is made up of 12 members appointed by the Executive Committee. In June 2024, the term of service of 6 members came to an end and the EC appointed 6 new members to replace them. We reproduce here the names of the incoming members of the SC. Outgoing Members Cheryl Hendricks Alice Karekezi Nacer Djabi Samuel Negash Fatima Denton Maitseo Bolaane Incoming Members of the Community Ismail Rashid Chikouna Cissé Mary Boatemaa Setrana Keneilwe Sadie Mooketsane Hlengiwe Portia Dlamini 6. Doyin Aguoro